2011
DOI: 10.1002/joc.2177
|View full text |Cite
|
Sign up to set email alerts
|

The influence of trees and grass on outdoor thermal comfort in a hot‐arid environment

Abstract: ABSTRACT:The effects of vegetation on human thermal stress in a hot-arid region were tested in two semi-enclosed urban spaces with various combinations of mature trees, grass, overhead shading mesh and paving. The index of thermal stress was calculated hourly from measured meteorological data in the studied sites to evaluate thermal comfort in the different spaces based on radiative and convective pedestrian-environment energy exchanges and sweat efficiency, and expressed on a thermal sensation scale ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
193
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(206 citation statements)
references
References 39 publications
7
193
0
6
Order By: Relevance
“…However, this study concurs with studies finding T s reduction from many types of shade (e.g., Antoniadis, Katsoulas, Papanastasiou, Christidou, & Kittas, 2015;Ketterer & Matzarakis, 2014b;Lin & Lin, 2010), where all shade, whether tree or artificial (e.g., mesh or shade sails), is found effective in reducing the T s in the hot and arid climate to safe levels. This would in turn reduce thermal discomfort from sensible heat fluxes as found in related shade studies (e.g., Antoniadis et al, 2015;Shashua-Bar et al, 2011). Further microclimate factors influencing heat stress and thermal discomfort-in addition to exchanges of solar radiation and sensible heat (via convection) discussed here-include evaporation and longwave emittance (Kenny, Warland, Brown, & Gillespie, 2009;Vanos, Warland, Kenny, & Gillespie, 2010), with metabolic activity increasing core and skin temperatures due to increased heat generation Yao, Lian, Liu, & Shen, 2007).…”
Section: Playground Design In Hot Climatesmentioning
confidence: 68%
See 1 more Smart Citation
“…However, this study concurs with studies finding T s reduction from many types of shade (e.g., Antoniadis, Katsoulas, Papanastasiou, Christidou, & Kittas, 2015;Ketterer & Matzarakis, 2014b;Lin & Lin, 2010), where all shade, whether tree or artificial (e.g., mesh or shade sails), is found effective in reducing the T s in the hot and arid climate to safe levels. This would in turn reduce thermal discomfort from sensible heat fluxes as found in related shade studies (e.g., Antoniadis et al, 2015;Shashua-Bar et al, 2011). Further microclimate factors influencing heat stress and thermal discomfort-in addition to exchanges of solar radiation and sensible heat (via convection) discussed here-include evaporation and longwave emittance (Kenny, Warland, Brown, & Gillespie, 2009;Vanos, Warland, Kenny, & Gillespie, 2010), with metabolic activity increasing core and skin temperatures due to increased heat generation Yao, Lian, Liu, & Shen, 2007).…”
Section: Playground Design In Hot Climatesmentioning
confidence: 68%
“…However, this cooling effect as studied costs a substantial amount of water to achieve-an expensive proposition in a desert city. Further bioclimatic design in hot and sunny climates must employ shade as a means of effectively reducing the mean radiant temperature imposed on a human at the hottest time of the day, and thus overall heat stress (Ali-Toudert & Mayer, 2007;Matzarakis & Endler, 2010;Shashua-Bar, Pearlmutter, & Erell, 2011). We show that shade generates a T s that is similar or lower than the reference temperature, T a , reversing the general trend where T s > T a .…”
Section: Playground Design In Hot Climatesmentioning
confidence: 82%
“…These findings agree with the interrelated effects of different surface characteristics previously identified by several studies. Shashua-Bar (2011) found that the actual microclimatic effects of vegetation are complex and interrelated with the effects of other built environments. Oke et al (1999) noted that typically, the sensible heat flux is likely to increase with impervious land cover, but at the same time, the relationship is influenced by water availability and the efficiency of storage.…”
Section: Land Cover Analysismentioning
confidence: 99%
“…green spaces and water bodies) can serve as key role in mitigating summer thermal loads. The positive effects of non-sealed surfaces and urban parks and gardens, especially in reducing temperatures through shading, evapotranspiration and cool-air production, are as well known as the cooling effects of urban water bodies (Saito et al, 1990(Saito et al, /1991Kuttler, 1991;Spronken-Smith and Oke, 1998;Upmanis, 1999;Saaroni and Ziv, 2003;Bongardt, 2006;Robitu et al, 2006;Pearlmutter et al, 2009;Lin et al, 2010;Hassaan and Mahmound, 2011;Peters et al, 2011;Shashua-Bar et al, 2011). In addition, positive effects may be observed in neighbouring developed areas, provided that the green space is of sufficient size, the wind speed is adequate and the buildings on the fringe of the area are appropriate (Eliasson, 1996;Bongardt, 2006;Ng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%